Staging urban landscapes the activation and curation of flexible public spaces - Ivers, B. Cannon (Birkhäuser, 2018)
Open urban spaces are an ideal stage for public events. An important prerequisite for their design in an increasingly heterogeneous multicultural cityscape is the relationship between design, use, and social function. The book documents both temporary as well as permanent installations of various kinds -- from the open-air courtyard of a museum to the design of a river bank promenade, through to a city park.